Absolute immature platelet count may predict imminent platelet recovery in thrombocytopenic children following chemotherapy1. Issue 7 (15th February 2013) - Have, Laerke Walther Junggreen; Hasle, Henrik; Vestergaard, Else Marie; Kjaersgaard, Mimi
Abstract Background Immature platelets are the youngest circulating platelets and they reflect the rate of thrombopoiesis. The immature platelet fraction (IPF) or the absolute immature platelet count (AIPC) may predict platelet count recovery following chemotherapy‐induced thrombocytopenia in pediatric patients and help guiding prophylactic platelet transfusion therapy. Procedure To test IPF and AIPC as predictors of platelet recovery, 19 children with platelet nadirs of less than 20 × 109/L after chemotherapy were prospectively enrolled. IPF, platelet count, and C‐reactive protein (CRP) were analyzed in 416 paired samples from 37 patients with malignancies to test if IPF‐levels were CRP dependent. Results A significant increase of 0.6 × 109/L in AIPC was seen between 1 and 2 days prior to platelet count recovery. No predictive day‐to‐day differences were found for IPF. Platelet count recovery did not occur significantly earlier for patients with a peak IPF > 10% than for those patients with a peak IPF < 10%. IPF and AIPC showed no correlation to CRP. AIPC was in contrast to IPF not influenced by platelet transfusions. Conclusion AIPC increased significantly between 24 and 48 hours before platelet recovery whereas IPF showed no significant increase during the same time period. AIPC may be a better indicator than IPF for predicting platelet recovery after chemotherapy in pediatric patients. Pediatr Blood Cancer 2013; 60: 1198–1203. © 2013 Wiley Periodicals, Inc.